The therapeutic mechanism of Chebulae Fructus in the treatment of immunosuppression in Chinese yellow quail on the basis of network pharmacology - Wu, Qiang; He, Min; Wang, Jing; Tong, TieJin; Yang, Dan; Tang, Huaqiao (Frontiers in Veterinary Science, 2023)
Introduction Chebulae Fructus (Terminalia chebula Retz.) is a well-known traditional Chinese medicine (TCM), one of the family Combretaceae, whose immature fruit is called Fructus Chebulae Immaturus or Zangqingguo. This present study aimed at detecting the target and therapeutic mechanism of Chebulae Fructus against immunosuppression through network analysis and experimental validation. Methods Effective components and potential targets of Chebulae Fructus were Search and filtered through the Chinese herbal medicine pharmacology data and analysis platform. A variety of known disease target databases were employed to screen the therapeutic target proteins against immunosuppression and thus constructing a protein-protein interaction network. Hub genes and key pathways in this study were identified by continuous project enrichment analysis. Further, the core targets and therapeutic mechanism of Chebulae Fructus against immunosuppression in Chinese yellow quail through animal experiment. Results Seventy-five identifiable major candidate targets of Chebulae Fructus were found and thus constructing a drug-compound-target-disease network. Targets derived from gene enrichment analysis play pivotal roles in lipid and atherosclerosis, fluid shear stress and atherosclerosis, and the hepatitis B pathway. Height of plicate and areas of lymphoid follicle were both increased and the expression of GATA-3 and T-bet was upregulated in Chinese yellow quail fed with Chebulae Fructus in animal experiment. Conclusion Chebulae Fructus may be a helpful Chinese medicine with immunosuppressive effect and prospective applications in future. Further research is also needed to understand the mechanisms of immunosuppression and the mechanism of action of immunomodulators.